1994
DOI: 10.1007/bf00192691
|View full text |Cite
|
Sign up to set email alerts
|

Swelling of wood

Abstract: The rate and maximum swelling of several North American wood species in water have been obtained with a computer interfaced linear variable displacement transformer. Since wood swells extremely fast in water even at room temperature, this apparatus made it possible for the first time, to obtain accurate rate data on the swelling of wood in water. The strict linear dependence of swelling on the temperature suggests a chemical mechanism. The activation energies obtained from Arrhenius plots ranged from 32.2 KJ/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(65 citation statements)
references
References 17 publications
2
63
0
Order By: Relevance
“…All of the lms exhibited greater swelling (approximately 1000% more) at 60 C than at 5 C, including the CNF-ref, which was initially considered to have no thermo-responsive properties. However, previous reports have shown that the swelling of wood occurred at faster rates with elevated temperatures in water, 47 and the same result has also been shown for various compressed cellulose bre pellets. 48 Moreover, this strong swelling dependence on temperature closely obeyed the classical Arrhenius equation, indicating that the swelling of wood was an activated process similar to a classical chemical reaction.…”
Section: Swelling Of Cnf Composite Lmsmentioning
confidence: 48%
“…All of the lms exhibited greater swelling (approximately 1000% more) at 60 C than at 5 C, including the CNF-ref, which was initially considered to have no thermo-responsive properties. However, previous reports have shown that the swelling of wood occurred at faster rates with elevated temperatures in water, 47 and the same result has also been shown for various compressed cellulose bre pellets. 48 Moreover, this strong swelling dependence on temperature closely obeyed the classical Arrhenius equation, indicating that the swelling of wood was an activated process similar to a classical chemical reaction.…”
Section: Swelling Of Cnf Composite Lmsmentioning
confidence: 48%
“…Since styrene is a hydrophobic molecule, it was dissolved in a good solvent for wood such as DMF or pyridine to maximize cell wall penetration. 22 The free radical polymerization of styrene was then conducted for 18 hours at 75 C (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…The molecules sizes of the treatment solution are important for easy penetration in wood structure. When greater or equal to 0.63 nm, penetration is difficult (Mantanis et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The first is that the solution should be sufficiently polar to exhibit a high affinity with wood hydroxyl groups; second, molecules must be soluble in a polar solvent; and third, a molecule's weight should be small enough to facilitate the penetration into the wood cell wall structure. The sizes of wood micropores are especially important (Mantanis et al 1994;Hill 2006). According to a study conducted by Hill (2006), the maximum size of wood cell wall micropores should be between 2 and 4 nanometers (nm).…”
Section: Introductionmentioning
confidence: 99%